Who provides physical activity support in the workplace? Implications for peer led interventions. (March 2020) - Edmunds, Sarah; Sitch, Matthew; Lowry, Ruth
Objective: Social support is one mechanism through which peer support physical activity (PA) interventions influence behaviour. The aim of this study was to explore the sources and characteristics of social support for PA among office-based work colleagues. Design: A sequential mixed-methods approach was used. First, social network analysis was utilised to map the sources of social support. Then interviews and focus groups were used to explore the characteristics of this support. Setting: One UK public sector employer in the south of England. Method: Using an online survey, 99 employees (40 men; M age = 40 ± 12 years) reported their PA and named specific colleagues who provided four forms of social support for PA (emotional, informational, companionship, validation). Social network diagrams for each support network were visualised using UCINET and Netdraw. Individuals identified as most frequently providing support for PA participated in one-to-one interviews ( n = 6) to discuss their perspective on social support for PA in the workplace. Three focus groups explored the characteristics of social support for PA among employees identified within the networks as support seekers or disconnected. These qualitative data were analysed thematically. Results: Different patterns of relationships between employees were demonstrated for the four forms of support with informational support provided most frequently and validation least frequently. Qualitative data illustrate how each form of support was provided and received, as well as further perceived characteristics of social support. Conclusion: These findings could help inform the future selection and training of peer PA champions in workplace settings and more widely.